2015
DOI: 10.1007/s11695-015-1800-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Gastric Banding 10 Years and Beyond

Abstract: The present investigation provides evidence that gastric banding remains effective after more than 10 years in less than 50 % of initially operated patients. Older (>50 years) and male patients seemed to maintain the banding as long-time carriers with good results, and these patients subjectively profited from this method. Good results can be achieved if patients are followed thoroughly, and alternative surgical options for patients who fail may be offered with longstanding success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
2
6
0
3
Order By: Relevance
“…years%EWL at max. years% re-operationsMiller, 2007 [30]Band5549210154628Favretti, 2007 [31]Band17919111283819Naef, 2010 [32]Band1619410284920Himpens, 2011 [33]Band1545412364860Stroh, 2011 [34]Band2008412153326O’Brien, 2013a [4]Band32278115544743O’Brien, 2013b [12]Band407810316354Aarts, 2014 [35]Band2019914883867Angrisani, 2013 [13]Band278110224641Arapis, 2017 [36]Band89790153484256Victorzon, 2013 [37]Band608815164748Kowalewski, 2017 [38]Band1079011372754Caradina, 2017 [39]Band3017915113860Toolabi, 2015 [40]Band802313184778Trujillo, 2016 [41]Band10073123366…”
Section: Resultsmentioning
confidence: 99%
“…years%EWL at max. years% re-operationsMiller, 2007 [30]Band5549210154628Favretti, 2007 [31]Band17919111283819Naef, 2010 [32]Band1619410284920Himpens, 2011 [33]Band1545412364860Stroh, 2011 [34]Band2008412153326O’Brien, 2013a [4]Band32278115544743O’Brien, 2013b [12]Band407810316354Aarts, 2014 [35]Band2019914883867Angrisani, 2013 [13]Band278110224641Arapis, 2017 [36]Band89790153484256Victorzon, 2013 [37]Band608815164748Kowalewski, 2017 [38]Band1079011372754Caradina, 2017 [39]Band3017915113860Toolabi, 2015 [40]Band802313184778Trujillo, 2016 [41]Band10073123366…”
Section: Resultsmentioning
confidence: 99%
“…Results regarding the long-term incidence of AGB explantation are contradictory. The majority have reported that about 50% of AGBs are explanted in the long-term (>10 years),45678910 whereas O'Brien, et al11 reported that only 5.6% of bands were explanted in a 10-year follow-up study of 714 patients and that the need for revision decreased as the technique evolved, with a 40% revision rate for proximal gastric enlargements during the first 10 years and a revision rate of only 6.4% during the last 5 years. In the present study, we investigated the incidences, types, and causes of AGB explantation over 10 years of clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Although band type and duration of follow-up differ between studies, fourteen out of seventeen series 11,14,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] identified by O'Brien et al 15 documented similar success. It also showed that close to 50% of type II diabetics were able to discontinue anti-diabetic medications.…”
Section: Discussionmentioning
confidence: 93%